Gene editing of angiotensin for blood pressure management - Stefano Masi; Hermann Dalpiaz; Claudio Borghi (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Arterial hypertension has remained the world's leading cause of morbidity and mortality for more than 20 years. While early Genome-Wide Association Studies raised the hypothesis that a precision medicine approach could be implemented in the treatment of hypertension, the large number of single nucleotide polymorphisms that were found to be associated with blood pressure and their limited impact on the blood pressure values have initially hampered these expectations. With the development and refinement of gene-editing and RNA-based approaches allowing selective and organ-specific modulation of critical systems involved in blood pressure regulation, a renewed interest in genetic treatments for hypertension has emerged. The CRISPR-Cas9 system, antisense oligonucleotides (ASO) and small interfering RNA (siRNA) have been used to specifically target the hepatic angiotensinogen (AGT) production, with the scope of safely but effectively reducing the activation of the renin-angiotensin system, ultimately leading to an effective reduction of the blood pressure with extremely simplified treatment regimens that involve weekly, monthly or even once-in-life injection of the drugs. Among the various approaches, siRNA and ASO that reduce hepatic AGT production are in advanced development, with phase I and II clinical trials showing their safety and effectiveness. In the current manuscript, we review the mode of action of these new approaches to hypertension treatment, discussing the results of the clinical trials and their potential to revolutionize the management of hypertension.